What can mathematical models bring to the control of equine influenza? - Daly, Janet M.; Newton, J.R.; Wood, J.L.N.; Park, A.W. (Wiley, 2013)
Mathematical modelling of infectious disease is increasingly regarded as an important tool in the development of disease prevention and control measures. This article brings together key findings from various modelling studies conducted over the past 10 years that are of relevance to those on the front line of the battle against equine influenza.